2021
DOI: 10.1103/physrevapplied.15.044050
|View full text |Cite
|
Sign up to set email alerts
|

Density of States of OLED Host Materials from Thermally Stimulated Luminescence

Abstract: The electronic density-of-states (DOS) plays a central role in controlling the charge-carrier transport in amorphous organic semiconductors, while its accurate determination is still a challenging task. We have applied the low-temperature fractional thermally stimulated luminescence (TSL) technique to determine the DOS of pristine amorphous films of OLED host materials. The DOS width is determined for two series of hosts, namely, (i) carbazole-biphenyl (CBP) derivatives: CBP, mCBP, and mCBP-CN, and (ii) carbaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Numerous studies have shown that examination of the density of states can explain the charge-transfer characteristics of organic semiconductors. 108 Indeed, it also provides the contribution of the MOs of each molecule's different components to the overall system. The GaussSum can be used to determine the density of states (DOS) function.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that examination of the density of states can explain the charge-transfer characteristics of organic semiconductors. 108 Indeed, it also provides the contribution of the MOs of each molecule's different components to the overall system. The GaussSum can be used to determine the density of states (DOS) function.…”
Section: Resultsmentioning
confidence: 99%
“…The agreement is good, especially at moderate field strengths. Equation 21 gives the correct value and field dependence of hole mobility in nonpolar organic material 4,4′-bis( N -carbazolyl)-1,1′-biphenyl (CBP), as measured in previous work, 30 providing the independently determined 31 values σ = 0.125 eV and μ 0 = 0.8 cm 2 V –1 s –1 . We obtain the inverse localization radius γ = 2.5/ a 0 from fitting; hence, ν 0 = 10 15 s –1 from eq 21 .…”
mentioning
confidence: 86%
“…The proposed approach has been tested by comparison with the known results of MC modeling of charge carrier mobility in organic quadrupole glasses (where a similar type of correlation exists). Using the same approach, an analytic model of the diffusion coefficient and mobility for quadrupole glasses has been developed and justified by comparison with the experimental data. , …”
mentioning
confidence: 99%
“…47 Recently the shape of the DOS in several organic glasses serving as the popular charge transporting materials has been studied. 48 In two materials with molecules having low dipole moments (i.e., the very type of the materials where we can expect the dominant quadrupolar contribution to the DOS) the exponential tails of the DOS have been observed, while for materials with molecules having high dipole moments the DOS has the Gaussian shape. Some degree of the local order is natural for the arrangement of spacious and highly asymmetric organic molecules, thus the development of the exponential tails seems to be a common phenomenon.…”
Section: Pccp Papermentioning
confidence: 98%